2023
DOI: 10.3389/fmed.2022.1062450
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Sotrovimab, remdesivir and nirmatrelvir/ritonavir combination as salvage treatment option in two immunocompromised patients hospitalized for COVID-19

Abstract: COVID-19 in immunocompromised patients is difficult to treat. SARS-CoV-2 interaction with the host immune system and the role of therapy still remains only partly understood. There are no data regarding the use of monoclonal antibodies and the combination of two antivirals in fighting viral replication and disease progression. We report the cases of two patients, both treated with rituximab for non-Hodgkin lymphoma and granulomatosis with polyangiitis, respectively, and both hospitalized for COVID-19 with posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…Both these two patients (number 1 and number 8 in Table 1) had persisting cough and CTS signs of Prior to this study, few case reports and small case series have described the management of patients with persisting infection with a wide range of therapeutic approaches. Prolonged courses of remdesivir 13 or nirmatrelvir/ritonavir, 14 dual antiviral therapy with remdesivir and nirmatrelvir/ritonavir, [15][16][17] and combination therapy with antiviral and monoclonal antibodies [18][19][20][21][22] have been described as treatment options. These studies have shown encouraging results, and they have provided valuable information for clinicians considering the lack of recommendations for these patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both these two patients (number 1 and number 8 in Table 1) had persisting cough and CTS signs of Prior to this study, few case reports and small case series have described the management of patients with persisting infection with a wide range of therapeutic approaches. Prolonged courses of remdesivir 13 or nirmatrelvir/ritonavir, 14 dual antiviral therapy with remdesivir and nirmatrelvir/ritonavir, [15][16][17] and combination therapy with antiviral and monoclonal antibodies [18][19][20][21][22] have been described as treatment options. These studies have shown encouraging results, and they have provided valuable information for clinicians considering the lack of recommendations for these patients.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] Therefore, in clinical practice, the predicted lack of evidence has resulted in the use of various off-label treatment approaches, including prolonged or reiterated single agent-based or combinationbased therapies. [13][14][15][16][17][18][19][20][21][22] In this scenario we introduced in our clinical practice the combination of two antiviral drugs, remdesivir and nirmatrelvir/ritonavir, in a selected subgroup of patients with severe impairment of adaptive humoral immunity and persistent SARS-CoV-2 infection. Patients urgently needing to resume the treatment of their original comorbidity were favored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the frequently observed recurrent and persistent pneumonia in immunocompromised COVID‐19 patients is caused by persistent active viral replication. There are several recent reports of the resolution of long‐term or combined antiviral therapy for COVID‐19 pneumonia in immunocompromised patients 23–25 . Further studies are needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cases have been reported in which strong anti-viral therapy, including the use of remidesivir and nirmatrelvir/ritonavir with or without sotrovimab, successfully eradicated the virus and prevented organized pneumonia in patients with prolonged COVID-19 infection. [29][30][31] We hypothesized that the residual virus in the lower respiratory tract and the production of in ammatory cytokines in response may contribute to the development of organizing pneumonia with brosis. Although early intervention with corticosteroids is effective in reversing pulmonary functional de cits in reports from the pre-Omicron era, 32 the use of high-dose corticosteroids is likely to compromise the potency of anti-viral therapy.…”
Section: Discussionmentioning
confidence: 99%